SONGKET TRADISIONAL PALEMBANG KAJIAN TENTANG NAMA, BENTUK DAN PENEMPATAN MOTIF - HESTI ROSITA DWI PUTRI, Dra. Ernis, M.Pd, Eliya Pebriyeni, S.Pd., M.Sn (Serupa The Journal of Art Education, 2014)
Palembang songket is cultural inheritance from ancestor as name, form and motif structure and also the technique of production. As passed, for many people, songket is interesting, but the people just know the name of songket, they do not know the motif of songket. One of the way for developing of traditional songket of Palembang is by knowing the names, the forms, and the motif structure of Palembang traditional songket.The purposes of this research are to: 1) describe the motif names ofPalembang traditional songket, 2) describe the motif forms of Palembang traditional songket 3) describe the motif structures of Palembang traditional songket. The method that is used in this research is a descriptive qualitative, which is a procedure of research for searching and describing situation in the field. The data result is collected by observation, interview and documentation. The samples of this research are the head UPTD of Museum Sultan Mahmud Badaruddin II Palembang, the artist and cultural observer of songket Palembang, the songket workers, the songket seller and the people that use songket.The result shows that the names of Palembang from Palembang traditional songket come from flora, fauna, and the natural names names (except flora and fauna). The name of Palembang traditional songket’s motif are 1)Limar mentok, 2)Tali air, 3)Tali air lurus, 4)Umpak pangkal, 5)Umpak ujung, 6)Puncak rebung, 7)Puncak rebung keris, 8)Tawur bunga melati, 9)Kucing tidok besak, 10)Ombakombak, 11)Talam, 12)Kembang pita, 13)Tretes, 14)Kembang setaman, 15)Bintang, 16)Rumpak ayam, 17)Pulir bali, 18)Bungo cino, 19)Bungo pacik, 20)Nago besaung, 21)Kemala, 22)Kumpe, 23)Batang bodi and 24)Lidi tigo. The forms of motif Palembang traditional songket are flora, fauna, natural (except flora and fauna) and geometri forms. The motif structures of the Palembang traditional songket are 1) the body of body, 2) the head of songket and 3) the edges of songket.Kata kunci: Nama, Bentuk, Penempatan Motif, Songket Tradisional Palembang